microRNA-194 is increased in polycystic ovary syndrome granulosa cell and induce KGN cells apoptosis by direct targeting heparin-binding EGF-like growth factor - Yi-xuan Wu (BMC, 2021)
Abstract Background Polycystic ovary syndrome (PCOS) is an endocrine-related follicular developmental disorder that affects 50 %-70 % of reproductive-aged women diagnosed with ovulation-related infertility. Abnormal proliferation and apoptosis of granulosa cells (GCs) are thought to be the critical factors leading to abnormal maturation of follicles. It has been shown that microRNAs (miRNAs) exert a significant influence in the pathogenesis of PCOS; however, the relationship between miRNA, PCOS, and GC apoptosis is not entirely understood. Methods To clarify the effect of miR-194 in PCOS, CCK-8, Ki67 staining, AO/EB, and flow cytometry assays were used to assess cell growth, proliferation, and apoptosis in KGN cells, which were artificially stimulated to overexpress miR-194. Luciferase reporter assays and rescue experiments were used to elucidate the mechanism underlying miR-194 in PCOS. Results miR-194 expression was significantly up-regulated in rat models of PCOS and the ovarian GCs of PCOS patients. miR-194 suppression promoted KGN cell growth and proliferation. miR-194 overexpression also induced cell apoptosis, while miR-194 downregulation had an opposite effect. Furthermore, up-regulating heparin-binding EGF-like growth factor (HB-EGF) expression rescued the pro-apoptotic effects of miR-194 upregulation on KGN cells. Conclusions miR-194 is increased in PCOS granulosa cell and may function as a novel biomarker and therapeutic target for KGN cells via HB-EGF regulation.